DEVELOPMENT OF A PADLET ASSISTED DIGITAL LEARNING RESOURCE INCORPORATING LOCAL ECOSYSTEM FOR IMPROVING LEARNING OUTCOMES IN BIOLOGY LEARNING - Kebeaken, Aloi Fitriani; Manurung, Binari (Universitas Bhinneka PGRI, 2026)
This study aims to develop and evaluate a digital learning resource based on the local Salib Kasih ecosystem supported by Padlet for biology learning. The development used the 4D model: Define, Design, Develop, and Disseminate. The product includes animated videos, educational posters, and quizzes integrated in Padlet. Validation by two experts resulted in very high feasibility scores (82.14% and 95.83%). Practicality was tested through teacher and student responses, showing the product is very practical. Effectiveness was measured using an independent sample t-test comparing posttest scores between experimental and control groups. The result showed a significant difference in learning outcomes (experimental mean = 84.34; control mean = 62.44; t = -7.800; p = 0.000 0.05), with an N-Gain of 0.70, categorized as high improvement. These findings indicate that the digital learning resource developed is feasible, practical, and effective in enhancing students’ understanding of biology using local ecosystem-based content.